A New Calculating Model for the Suitable Area of Air Cleaners Purifying Indoor Gaseous Chemical Contaminants. (2015) - Yin, Xiaotong; Liu, Junjie; Pei, Jingjing; Hou, Yuefei
Abstract: Suitable area is an important index when selecting air cleaners. The suitable area's models in corresponding standards in American, Canada and Japan are all set up according to the particulate matters concentration equation. The suitable area can be calculated by multiplying a coefficient with CADR. However, air cleaners are also used to remove indoor gaseous chemical contaminants. The suitable area for particulate matters may not be reasonable for gaseous chemical contaminants. A new model to calculate the suitable area for indoor gaseous chemical contaminants has been set up. Using the CADRs of six tested air cleaners on the market, we compared the suitable areas of the air cleaners in different contaminant concentration levels. The results show suitable areas for gaseous chemical contaminants are much smaller than those for particulate matters. It is of great importance to distinguish suitable areas for different contaminants and the new model has a great reference value.